Synthesis of Nanocarbons Using a Large Volume AC Plasma Reactor. Issue 1747 (10th April 2015) - Hamady, M.; Sheppard, D.; Seddighi, K.; Sarawagi, A.; Scott, B.; Wilcox, K.; Gerber, A.; Chibante, L.P.F.
ABSTRACT: There is an opportunity for scaling up, optimizing, and controlling the process of production of nanoparticles due to their numerous diverse applications. We present a system for continuous, high rate production of nanoparticles, particularly those of carbon, using large volume thermal plasma based on a three-phase diverging electrode configuration. The goal of using this 3-phase plasma reactor is to have a plasma arc that is scalable, self-stabilizing, and low maintenance, with sufficient plasma volume to maximize residence time of feed materials for evaporation to atomic species. Plasma carrier gas, typically inert gas such as helium, is injected into the reactor allowing the vaporization of any feedstock due to plasma temperatures >5000 °C. Controlling plasma enthalpy, diffusion/temperature gradients and carbon feed rates allow the controlled growth of clusters leading to nanoparticles less than 100 nm. Once the desired size is achieved the gas stream is expanded to reduce the reaction rate and quenched by natural cooling to chamber walls or injection of a cooling gas stream, preferably of the same composition as plasma carrier gas. Recoverable yields in the nanoparticle-laden gas stream are then isolated by standard means (filtration, cyclone separation, electrostatic precipitation), and the plasma gas and unreacted feedstock are routed to the plasma reactor for recycling. Computational Fluid Dynamics (CFD) is employed to measure and predict fluid flow, energy/temperature, and other species distributions in the plasma process.